THE ROLE OF THE FAMILY IN RESPONDING TO RADICAL IDEOLOGIES - Dewi Nur Aeni; Ais Chusniati; Duta Sukma Yoga; Faiqotun Khasanah; Yessica Dwi Elvira (IAIN Batusangkar, 2021)
This study aims to describe and analyze what efforts can be made by families regarding their role against radical ideology in children. The role of the family is the first step that can be taken and usually implemented in the form of fostering and inculcating contextual religious teachings from an early age. In the family, the role of parents is prioritized because they are the ones who play an active role in the character building, personality, and morality of children. So that children can distinguish between good and bad things in the process of growth and development. Thus, children can avoid the influence of radical ideologies that develop in society. In this study, the authors use journal literature and effective data that are relevant to the problem, namely the role of the family against a radical ideology which then qualitatively explains the result that we got. The results of this study illustrate the importance of the role of the family, that is parents in raising children by inculcating the values that need to be taught to children, and the efforts made by families in countering radicalism.